ETIKA DAN STRATEGI PUBLIKASI ILMIAH BAGI MAHASISWA KELAS RISET FAI: DARI PENULISAN HINGGA SUBMIT KE JURNAL TERAKREDITASI NASIONAL - Mukhlishin Mukhlishin; Ahmad Hulaimi; Syaharuddin Syaharuddin; Suhadah Suhadah; Sukarta Sukarta; Muhammad Musfiatul Wardi (STKIP PGRI SITUBONDO, 2026)
Scientific publishing skills are one of the important competencies that students must have, especially in the digital age, which demands high academic literacy and writing ethics. This activity aims to improve students' hard skills and soft skills in writing, managing references, and understanding the ethics and procedures of scientific publishing. The methods used in this program are workshops and hands-on practice, which are designed to be practical so that participants can apply the material in real-world contexts. This activity was attended by 45 research class students from the Faculty of Islamic Studies who already had a foundation in academic writing but were not familiar with the process of publishing in reputable scientific journals. The activity was evaluated through questionnaires and direct observation of participants' skills before and after the training. The evaluation results showed an average increase in competence of 82.33%, with the highest achievement in the aspect of mastery of digital publication tools (83.72%) and the lowest achievement in the aspect of understanding article submission procedures (79.53%). Overall, this activity proved to be effective in improving students' abilities in ethics, strategies, and technicalities of scientific publication based on SINTA journals.